AN EXAMINATION OF THE IMPACT OF PRICE LEVEL AND HALAL CERTIFICATION ON PURCHASE DECISION OF ‘ANGKRINGAN FOOD’ MSME’s - Nurwijayanto, Putra Ramadhani; Audia, Syahva; Setyawati, Dyah; Galih, Aditya; Sonalitha, Elta (Airlangga International Journal of Islamic Economics and Finance, 2024)
This research investigates the impact of price levels and halal certification on consumer purchasing decisions at Angkringan Tenda Mak Gendut, an SME in Malang City. Angkringan, a traditional Javanese street food stall, serves as a focal point for local communities and embodies Javanese culinary culture. Using Price Level, Halal Certification, and MSMEs Purchase Decision as variables, a quantitative approach was employed through an online questionnaire survey. Multiple linear regression analysis was conducted to analyze consumer preferences and purchasing behaviors. The findings reveal that both price level and halal certification significantly influence customer purchasing decisions, underscoring the importance for MSMEs to carefully manage pricing strategies and maintain high halal standards to attract and retain customers. These insights highlight the dual role of affordability and halal certification in shaping consumer choices, essential for enhancing MSMEs' market competitiveness and consumer appeal.